Kehidupan Sosial Ekonomi Buruh Pesapon Wanita: Studi Pada Dinas Lingkungan Hidup dan Kebersihan/DLHK Pangandaran - Rima Alami; Muhamad Rizal; Sari Usih Natari (Yayasan Daarul Huda Kruengmane, 2023)
This study aims to determine the social and economic conditions of workers or female workers at the Department of Environment and Sanitation/DLHK Pangandaran. After the Covid-19 pandemic hit in 2019, the world's economic system declined, especially in Pangandaran Regency. This is felt directly by residents around Pangandaran such as female workers/workers who must meet the needs of their families to remain stable. The negative impact of the covid-19 pandemic is the length of time the wage process will be received by these workers. Besides working here, they have side jobs to cover the difficulties of late receipt of wages such as having a business at home, farming or being a household assistant. They have been doing this up to now.